PEMBINAAN KARAKTER SEMANGAT KEBANGSAAN MELALUI PEMBIASAAN UPACARA BENDERA HARI SENIN DI SD NEGERI SERANG 20 - Aulia, Fadhila Nurul; Syahbani, Nisfa Laila; Dilah, Salsa; Robiansyah, Firman (STKIP Persada Khatulistiwa Sintang, 2024)
The current conditions show a decrease in character, including the character of national spirit. The efforts are needed to develop this character. The aim of this research is to find out how the ceremony is carried out at SD Negeri Serang 20 and the implications of holding the flag ceremony on Monday for developing the character of the national spirit of students at SD Negeri Serang 20. This research applied qualitative research with a case study method. The subjects of this research were the principal, class teacher VIB, and 100 students from classes IVA, IVB, VA, VB, VIA, and VIB located at SD Negeri Serang 20. Methods of observation, interviews, and distributing questionnaires were used to obtain the required data of this investigation. Then the data was analyzed using the Miles and Huberman model data analysis technique. Monday's flag ceremony starts at 07.00-07.40 WIB which includes preparation, implementation of the main event, and conditioning for each classes. Based on the results of observations and interviews, it can be proven that Monday flag ceremony can foster the character of the national spirit in SD Negeri Serang 20. Then this implication is strengthened by the results of the questionnaire which shows that 91% of students answered correctly and 9% of students answered incorrectly. It can be concluded that Monday's flag ceremony shows significant implications for the development of national spirit character.